DETERMINANT ANALYSIS OF HUMAN DEVELOPMENT INDEX IN OF NORTH SUMATERA PROVINCE - Butar Butar, Ribka Sari (Universitas Negeri Medan, 2019)
The results showed that the number of poor people and government expenditures from the aspect of health funds had a significant effect on the HDI. While open unemployment and government spending from the aspect of education fund did not significantly affect the Human Development Index. The success of the economic development of a region can be seen from the high economic growth, with the increase of economic growth is expected also can improve the welfare of society and increase human development with indicator of Human Development Index (HDI).